Physicochemical Properties, Metal Availability, and Bacterial Community Structure in Cadmium-Contaminated Soil Immobilized by Nano-Montmorillonite - Liu, Wei; Zhao, Chenchen; Yuan, Yanli; Song, Xinpeng; Zhao, Huiwei; Wang, Shutao (Frontiers in Environmental Science, 2022)
Montmorillonite has been widely used to remediation toxic metals. However, for the safety of the soil ecosystem, the impact of this technology on microorganisms is still unclear. Here, the influence of nano-montmorillonite on immobilization, accumulation of cadmium and microbial activity in a soil-plant system. The results revealed that the nano-montmorillonite treatments reduced cadmium bioavailable and the uptake by oilseed rape. It was found that the addition of NMMT reduced the toxicity of Cd on soil microorganisms and improved enzyme activity. The nano-montmorillonite stimulated the relative abundance of Proteobacteria that was closely related to nutrient turnover in soil. In addition, the treatment with the 0.5% addition of nano-montmorillonite significantly improved the microbial alpha diversity index and enhanced the relative abundance of Bacteroidetes and Planctomycetes. Thus, certain soil quality recovery occurred after the application of nano-montmorillonite. To successfully combine remediation and microbial effects, 0.5% nano-montmorillonite was recommended to add to cadmium contaminated soil to minimize the additional impact on the soil ecosystem.